Candidemia in cancer patients: phenotypical and molecular-genetic characteristics of antifungal drug resistance, pathogenic factor genes of Candida spp. - N. S. Bagirova; E. A. Goremykina; P. V. Slukin; O. E. Khokhlova; N. K. Fursova; I. N. Petukhova; Z. V. Grigorievskaya (Сибирский онкологический журнал, 2022)
Relevance. The global trend of rapid increase in resistance to antifungal drugs due to multiple factors, dictates the need for continuous monitoring of taxonomic structure and susceptibility of nosocomial pathogens, causing invasive fungal infections, for permanent correction of the optimal prevention and treatment strategies.Purpose: to determine antifungal susceptibility of the main yeast pathogens in candidemia in cancer patients, as well as to determine resistance genes and pathogenic factor genes.Material and Methods. Eighty-two strains of Candida spp. isolated from blood of cancer patients from 2015 to 2021 were analyzed. Minimum inhibitory concentrations of fuconazole, voriconazole, posaconazole, anidulafungin and micafungin were determined by a gradient method (E-test, BioMerieux, France). The EUCAST and CLSI criteria were used for MIC value assessment. The genes, associated with pathogenicity factors, and resistance to antifungal drugs were identifed.Results. Our study results based on EUCAST 2020, v.10.0 criteria showed that triazoles, especially fuconazole, were the least effective drugs in empirical therapy for invasive candidiasis (including candidemia). Resistance of Candida spp. fuconazole was superior to that of voriconazole (47.2 % vs 23.2 %, respectively, p<0.01) and posaconazole (47.2 % vs 30.4 %, respectively, p><0.05). The highest in vitro activity was observed in echinocandins, and anidulafungin was 2 times more active than micafungin (4.1 % of resistant strains vs 11.4 %, respectively), with no statistically signifcant difference (p>0.05). The ERG11 and FKS1 genes associated with resistance to antifungal drugs were detected in 28.6 % of Candida spp. strains. The ERG11 gene was detected in 8.6 % of cases, exclusively in Candida albicans strains. The FKS1 gene was identifed in 20.0 % of strains (85.7 % of them were C. parapsilosis, 7.1 % each were C. tropicalis and C. glabrata). Pathogenic factor genes were identifed in 78.6 % of C. albicans and in 79.1 % of C. parapsilosis strains.Conclusion. Molecular genetic methods for the detection of Candida spp strains carrying resistance genes to antifungal drugs, and the determination of pathogenicity factors are promising trends in searching for biomarkers. They facilitate interpretation of results of microbiological study to assess the ability of Candida spp. strains to develop invasive mycoses.